KOMPOSISI SEMUT (HYMENOPTERA:FORMICIDAE) PERMUKAAN TANAH DI KEBUN GAMBIR DI KANAGARIAN SIGUNTUR MUDA KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Ramadanu, Riski; Nurhadi, Nurhadi; Safitri, Elza (STKIP PGRI Sumbar, 2013)
Abstract:Role of ants in nature can provide positive and negative effects on animals and humans. Positive benefits such as its role as a predator, decompose organic matter, pest control and even help pollination. Changes in forest areas into agricultural land, plantations often change roles Ants become pests. Changes gambier plantation forests to affect the existence of Ants. Composition studies Ants ( Hymenoptera : Formicidae ) in the Garden Ground in Kanagarian Siguntur Young Gambir subdistrict Koto XI Tarusan South Coastal District which was held in August- September 2013. This study uses a descriptive survey method. Sampling sites in this study consists of two stations that I garden Gambir station and the second station nearby forest garden gambir.pengambilan samples wa conducted by Ants Pifall trap vessel fitted with a tin roof that had been attached to the rafters. The distance between the zinc roof and land surface 15 cm, which consists of 3 substations. Distance between subsasiun 20 m. Based on the research that has been done on the composition of ants ( Hymenoptera : Formicidae ) in Garden Gambir subdistrict Kenagarian Young Siguntur Koto South Coastal District XI Tarusan inferred composition of ants were found in the garden belonging to the Gambir 4 subfamily, tribe 9, 14 genera, 18 species and as many as 106 individuals. Anoplolepis gracilipes density is 13,80 is the highest compared to other species , and a low of Leptogenis dinimus is 1.61. While the highest frequency is Anoplolepis gracilipes is 20.28, while the lowest was 2.37 Leptogenis dinimus. Soil physico-chemical factors have an important role for the existence of such ant soil temperature, soil moisture content, soil pH, and soil organic C content. In such circumstances gambir garden is perfect for the presence of ants.Â Â